National Commission For Refugees, Migrants, And Internally Displaced Persons (NCRMIDP) And Irregular Migration In Nigeria (Journal of Namibian Studies : History Politics Culture, 2022)
Both regular and irregular migration remain among the most divisive issues among states today. Though not a new phenomenon, migration flows have been increasing over the last three decades. Besides, since 9/11 and the subsequent ‘Global War on Terrorism’, migration has become an intense object for security analysis as it is undeniable how terrorism shape’s public opinion on migration and affects political movements inside civil society and party systems. Therefore, this study examined the roles of the role of the National Commission for Refugees, Migrants, and Internally Displaced Persons in curbing Irregular Migration that has posed threat to Nigeria’s National Security. The data for this study were collected from various secondary sources such as textbooks, journals, Reports from the International Office on Migration and other internet sources. Moreover, content analysis was employed in analysing the data collected. The human security approach was employed in this study.  This study revealed that the National Commission for Refugees, Migrants, and Internally Displaced Persons has played important role in curbing the inflow of irregular migrants but their efforts have been impeded by the porous nature of the Nigeria borders and patchy data from the Nigerian Immigration Service (NIS) on immigrants into Nigeria among others. Also, the study further shows that irregular migration has poses enormous threat to Nigeria’s national security. Thus, calling for urgent effort by the Nigerian state.  This study recommends among other things that there is the need to enhance Nigeria border management through increased and targeted training of staff of the National Commission for Refugees, Migrants, and Internally Displaced Persons and the Nigeria Immigration Service (NIS).